Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 15 - Differentiation in Several Variables - 15.3 Partial Derivatives - Exercises - Page 781: 51


$$\frac{\partial W}{\partial E} =-\frac{1}{kT}e^{-E/kT},$$ $$\frac{\partial W}{\partial T} =\frac{E}{kT^2}e^{-E/kT}.$$

Work Step by Step

Since $ W=e^{-E/kT}$, then using the chain rule, we have $$\frac{\partial W}{\partial E}=e^{-E/kT} (-1/kT)=-\frac{1}{kT}e^{-E/kT},$$ $$\frac{\partial W}{\partial T}=e^{-E/kT} (E/kT^2)=\frac{E}{kT^2}e^{-E/kT}.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.